Evaluation of Commercial Syrup as a Stimulant Additive to Improve Elephant Grass Silage Quality: Evaluasi Sirup Komersial Sebagai Aditif Stimulan untuk Meningkatkan Kualitas Silase Rumput Gajah - Sadarman, Sadarman; Febrina, Dewi; Handoko, Jully; Maharaja, M. Adil; Qomariyah, Novia; Gholib; Adegbeye, Moyosore Joseph; Harahap, Rakhmad Perkasa; Aprilliza AM, Mozart Nuzul; Nurfitriani, Rizki Amalia (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
Elephant grass is a common forage for livestock fodder, yet it is prone to damage and requires preservation through silage-making techniques. This study was investigating the potential usage of expired commercial syrup (ECS) as a source of glucose in elephant grass silage production. The research used a Completely Randomized Design with five treatments and five replications. Treatments included a control group that consist of elephant grass (P1/control), and four supplemented grasses with ECS at levels of 2.50% (P2), 5% (P3), 7.50% (P4), and 10% (P5) based on dry matter (DM). After ensiling for 30 days at room temperature, various parameters were measured, i.e. aroma, texture, color, fungal growth, pH, dry matter, dry matter loss (DML), and fleigh value. Data were analysis using analysis of variance, followed by Duncan's test. The results revealed that ECS incorporation up to 10% DM had a significant influence on the evaluated parameters (p<0,05). The results showed P5 received the highest ratings from panellists for aroma (3.75; distinctive fermented acidity), texture (3.61; fine and non-clumping), and color (3.54; green). Additionally, P5 exhibited minimal fungal growth (1.57%), an optimal pH range (3.24-4.56), the highest dry matter content (31.4%), the lowest dry matter loss (2.27%), and the highest fleigh value (138). The research concluded that expired commercial syrup could use as a stimulant additive in elephant grass ensiling, effectively. Key words: elephant grass, expired commercial syrup, fungal growth, physical quality, silage